Evaluation of Correlation between Sleep and Psychiatric Disorders in a Population of Night Shift Workers: A Pilot Study - Cirrincione, Luigi; Plescia, Fulvio; Malta, Ginevra; Campagna, Marcello; Lecca, Luigi; Skerjanc, Alenka; Carena, Elisa; Baylon, Vincenzo; Theodoridou, Kelly; Fruscione, Santo; Cannizzaro, Emanuele (International journal of environmental research and public health, 2023)
Background: Insomnia is the perception of inadequate, insufficient or non-restorative sleep. Of all sleep-related disorders, insomnia is the most common. It is important to remember that the sleep–wake cycle also plays a central role in the genesis of anxiety and depression. The aim of our study is to evaluate the association between sleep disturbances and anxiety and depression in a group of workers of both sexes who perform night shift work. Methods: Information on sleep disorders was collected by administering the Insomnia Severity Index (ISI) questionnaire. Statistical analysis was conducted using the Chi-square test to assess whether there were any differences between sex for those who were healthy or who were diagnosed with psychiatric disorders. Results: The results showed that there was a good percentage of subjects with insomnia problems, impairing normal daily activities and promoting the onset of fatigue, daytime sleepiness, cognitive performance deficits and mood disorders. Conclusion: We highlighted how anxious and depressive anxiety disorders are more pronounced in people who suffer from altered sleep–wake rhythms. Further research in this direction could prove to be fundamental for understanding the genesis of the onset of other disorders as well.